Positive effects of the progestin desogestrel 75 μg on migraine frequency and use of acute medication are sustained over a treatment period of 180 days - Merki-Feld, Gabriele S (J Headache Pain, 2015)
BACKGROUND: Premenopausal migraines frequently are associated with fluctuations of estrogen levels. Both, migraine and combined hormonal contraceptives (CHC) increase the risk of vascular events. Therefore progestagen-only contraceptives (POC) are a safer alternative. A previous short-term study demonstrated a positive impact of the oral POC desogestrel on migraine frequency. To study the effect of the POC desogestrel 75 μg on migraine frequency, intensity, use of acute medication and quality of life in a clinical setting over the period of 180 days. METHODS: Patients’ charts were screened for women with migraine, who had decided to use desogestrel for contraception. Charts were included, if routinely conducted headache diaries were complete for 90 days before treatment (baseline) and over a treatment period of 180 days. We also report about starters who stopped treatment early, because of adverse events. Baseline data (day 1–90 before treatment) were compared with first and second treatment period (treatment days 1–90 and days 91–180). Quality of life was evaluated using MIDAS questionnaires. RESULTS: Days with migraine (5.8 vs 3.6), with any kind of headache (9.4 vs 6.6), headache intensity (15.7 vs 10.7), days with severe headache (5.4 vs 2.4) and use of triptans (12.3 vs7.8) were significantly reduced after 180 days. MIDAS score and grade improved significantly. CONCLUSION: Contraception with desogestrel 75 μg resulted in a significantly improved quality of life and a reduction of migraine days over the observation period of 180 days. A clinically meaningful 30% reduction in pain was observed in 25/42 (60%) participants. For counselling reasons it is of importance, that the major reduction in migraine frequency occured during the initial 90 days, however further improvement occurs with longer duration of use. Prospective studies are needed to confirm these results.